Low Temperature CO Oxidation Over Highly Active Gold Nanoparticles Supported on Reduced Graphene Oxide@Mg-BTC Nanocomposite - Altass, Hatem M.; Ahmed, Saleh A.; Salama, Reda S.; Moussa, Ziad; Jassas, Rabab S.; Alsantali, Reem I.; Al-Rooqi, Munirah M.; Ibrahim, Amr A.; Khder, Menna A.; Morad, Moataz; Ahmed, Awad I.; S. Khder, Abdelrahman (Catalysis letters, 2023)
In this study, gold nanoparticles (Au NPs) were successfully supported on reduced graphene oxide (rGO) and Mg-BTC in one pot under solvothermal conditions. The catalysts contain different amounts of Au NPs started from 1.0 up to 7.0 wt%. All of these catalysts were characterized by different techniques such as XRD, BET, TEM, SEM, XPS and TGA. The results exposed that the Au NPs were extremely dispersed on the surface of rGO@Mg-BTC catalyst as displayed in TEM and SEM images. Moreover, the XPS study showed proved the existence of both Au 0 , Au 1+ and different surface oxygen species on the catalyst surface. CO oxidation as a model reaction was then used to evaluate the catalytic activity of the as-synthesized composites. The results showed the main and vital role of Au NPs, their distribution and oxidation state in the oxidation of CO gas at low temperatures. Where the study proved the presence of both Au 0 particles and surface oxygen species on the surface increases the rate of adsorption and oxidation of CO gas. The study also showed that these catalysts prepared in one pot have outstanding stability with the possibility of reuse up to ten times without losing their catalytic activity. Which makes these catalysts have a high efficiency in protecting the environment from the poisonous CO gas. Graphical Abstract